MiR‐145 sensitizes ovarian cancer cells to paclitaxel by targeting Sp1 and Cdk6. Issue 6 (28th April 2014) - Zhu, Xiaolan; Li, Yuefeng; Xie, Chanjuan; Yin, Xinming; Liu, Yueqin; Cao, Yuan; Fang, Yue; Lin, Xin; Xu, Yao; Xu, Wenlin; Shen, Huiling; Wen, Jian
<x xml:space="preserve">Abstract</x> Multidrug resistance (MDR) remains a major obstacle to effective chemotherapy treatment in ovarian cancer. In our study, paclitaxel‐resistant ovarian cancer patients and cell lines had decreased miR‐145 levels and expressed high levels of Sp1 and Cdk6. Introducing miR‐145 into SKOV3/PTX and A2780/PTX cells led to a reduction in Cdk6 and Sp1 along with downregulation of P‐gp and pRb. These changes resulted in increased accumulation of antineoplastic drugs and G1 cell cycle arrest, which rendered the cells more sensitive to paclitaxel in vitro and in vivo. These effects could be reversed by reintroducing Sp1 or Cdk6 into cells expressing high levels of miR‐145, resulting in restoration of P‐gp and pRb levels. Furthermore, we confirmed that both Cdk6 and Sp1 are targets of miR‐145. Intriguingly, demethylation with 5‐aza‐dC led to reactivation of miR‐145 expression in drug‐resistant ovarian cancer cell lines, which also resulted in increased sensitivity to paclitaxel. Collectively, these findings begin to elucidate the role of miR‐145 as an important regulator of chemoresistance in ovarian cancer by controlling both Cdk6 and Sp1.